The Use of Drilling Techniques in Teaching Speaking at Eleventh Grade Students of MA Al-fatah - Khikmiyah, Siti; Hendrianto, Rama Bintang (Language Center of Islamic Institute of Uluwiyah (IAI Uluwiyah) Mojokerto Indonesia, 2023)
Abstract: Teaching English Speaking to the Senior High School need more effort and unique technique. Teachers can not use the same technique in teaching speaking to the adolescence and Senior High School Students. It needs different technique and instructional media to make them interested in learning English speaking. This research attempts to report what appropriate teaching technique and instructional media which are applied by an English teacher at MA Al-fatah Mojokerto. In this research, the researcher focuses on two research questions, there are what the English Speaking Teaching Technique used by the teacher at MA Al-fatah. And what media that is used by the teacher in teaching English Speaking to the eleventh grade of MA Al-Fatah. The researcher employs a qualitative descriptive study to answer those two questions which was held during August-September 2023. The result of this research is proved that Drilling Techniques is an appropriate Technique in Teaching English Speaking to the eleventh grade of MA Al-Fatah. Meanwhile, the appropriate media which is used by the teacher in teaching English Speaking to the eleventh grade is picture. In conclusion, by using drilling technique and pictures, the process of teaching English Speaking to the young learners becomes more interesting and enjoyable, so the students’ English speaking skill is improved. Keywords: drilling technique, teaching English speaking